Muscular pain among dentists - a pilot study / Faezah Sabirin, Siti Sarah Abdul Ahmad and W. Zahira Akmal W. Kamarudin - Sabirin, Faezah; Abdul Ahmad, Siti Sarah; W. Kamarudin, W. Zahira Akmal (2015)
Background: Muscular pain is the most common symptom associated to muscular skeletal disorders (MSDs). Dentists were exposed to ergonomic hazards while treating the patients. Without proper dental ergonomics, they are predisposed to the MSDs. Objective: This present study was designed to analyse the prevalence of muscular pain among practising dentists in Universiti Teknologi MARA (UiTM) and it relatedness to ergonomic factors. Methodology: A total of 25 dentists were participated in this pilot study. The inclusion criteria include working experience of at least six months and those who were readily diagnosed with musculoskeletal disorders were excluded. A self-administered questionaire was employed to gather demogaphic informations and close ended ("yes" or "no") questions were asked to assess the muscular pain experienced in the last 12 months. The collected data were then analysed statistically. Result: The result showed a 100% response rate. 92% of the respondents were reported to experience muscular pain, particularly on the upper body parts. Only maintenance of same postures without microbreaks and performing torsions or cervical flexions to improve vision of oral cavity correlate significantly (P<0.05) to the presence of muscular pain that respondent experienced. However, age, nature of work and high woking hours per weeek does not correlate to the muscular pain. Conclusion: The prevalence of muscular pain among dentists in UiTM is high which indirectly suggested the lack of dental ergonomic awareness and practice in their routine at work.